Keadilan Ekonomi di Tinjauan Kesempatan Kerja dan Pengangguran - Muhdar Muhdar (Al-Buhuts, 2016)
The economic fairness a country happen, if the needs of all citizens are met. However, that requirement would be difficult to achieve if unemployment is still going on. Unemployment can be a devastating impact on the economy as well as individuals and society that should be addressed in accordance with the types of unemployment such as the type of frictional unemployment, structural,and cyclical. To overcome this problem, first, the government needs to implement fiscal policy by adjusting spending and taxes by the government with the aim to boost aggregate demand so that domestic output and employment increased. Second, the government needs to implement monetary policy by increasing the money supply to lower interest rates and increase the aggregate demand for products and services produced. Besides, it also provides enough jobs to all existing labor force; increase the availability of job information and qualifications needed working world; to provide guidance to the labor force; balancing rules on employment opportunities; avoid discriminatory the use of labor and promotion of based on race or gender; designing of training program to improve the skills and work experience for unemployed the labor force is structurally; the government directly of hired and trained unemployed in the long term structural; provides wage subsidies or tax reductions directly; pay directly or cut taxes to be paid companies that employ groups particularly unfavorable. Wisdom from the supply side; deliberate action by the government to increase the supply of labor, savings and investments to reduce the cost of producing goods and services that aggregate supply curve moves to right. The government directly employing people who are not able to get a job.